Pengaruh Pembelajaran Matematika dengan Pendekatan Realistik terhadap Hasil Belajar Matematika Peserta Didik - Elis Yusimarliah (Universitas Indraprasta PGRI, 2015)
The aim is to examine the different of math learning outcome using realistic mathematics education and conventional learning. This research used true experimental designed through pretest-posttest control group designed, there is experiment and control classed which is used as sample classes. Two sample classes were taken from three parallel class through random class sample. Collecting the data by using learning outcome in essay form. Data analysis through ttest, which examined normality and homogeneity. The result shows that learning mathematic through realistic mathematics education is higher than learning mathematic through mechanistic approach.